(untitled) (Journal of Universal Science Research, 2024)
A price bubble is beginning to build in the real estate market when housing prices rise more quickly than local wages and rents. A "bubble" occurs when assets are consistently valued below their true worth; their presence cannot be established until it collapses. With several interconnected origins and reinforcing processes, the housing price bubble is a complex phenomenon that had a role in the global financial and economic crisis of 2007–2009[1].